2020
DOI: 10.1038/s42004-020-00375-0
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-supported ultra-small nickel as catalyst for selective oxidation of methane to syngas

Abstract: The development of simple catalysts with high performance in the selective oxidation of methane to syngas at low temperature has attracted much attention. Here we report a nickel-based solid catalyst for the oxidation of methane, synthesised by a facile impregnation method. Highly dispersed ultra-small NiO particles of 1.6 nm in size are successfully formed on the MOR-type zeolite. The zeolite–supported nickel catalyst gives continuously 97–98% methane conversion, 91–92% of CO yield with a H2/CO ratio of 2.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Methane (CH 4 ), the main component of natural gas, has attracted increasing attention in the chemical industry, as it can be converted to fundamental chemical products such as methanol, olefins, Fischer–Tropsch (FT) oil, and acetic acid. Syngas is a mixture of CO and H 2 that is a common intermediate to manufacture the aforementioned chemicals. , Steam reforming of CH 4 (SRM, eq ) and its modified processes have been implemented to produce syngas for a long time. , However, SRM is an endothermic reaction operated at a temperature above 800 °C, which results in large energy consumption and high cost. Alternatively, partial oxidation of methane (POM) to syngas (formally eq ) is a potentially efficient method to reduce energy consumption. …”
Section: Introductionmentioning
confidence: 99%
“…Methane (CH 4 ), the main component of natural gas, has attracted increasing attention in the chemical industry, as it can be converted to fundamental chemical products such as methanol, olefins, Fischer–Tropsch (FT) oil, and acetic acid. Syngas is a mixture of CO and H 2 that is a common intermediate to manufacture the aforementioned chemicals. , Steam reforming of CH 4 (SRM, eq ) and its modified processes have been implemented to produce syngas for a long time. , However, SRM is an endothermic reaction operated at a temperature above 800 °C, which results in large energy consumption and high cost. Alternatively, partial oxidation of methane (POM) to syngas (formally eq ) is a potentially efficient method to reduce energy consumption. …”
Section: Introductionmentioning
confidence: 99%
“…Various metal supported catalysts for the oxidative reforming of methane have been investigated by many researchers. Rh is one of the active metal species for the reaction and has been widely utilized. , In general, thermally stable metal oxides such as Al 2 O 3 , MgO, ZrO 2 , and CeO 2 were used as supports. ,,, Zeolites are also thermally stable materials with large surface areas owing to their porous structures. Metal cations and clusters as active sites can be created by ion-exchange treatment. , In a previous study, Hou et al reported a MOR-type zeolite-supported Rh subnanocluster as a highly active catalyst for the selective oxidation of methane to syngas, and almost equilibrium CO yield at 600 °C was achieved .…”
Section: Introductionmentioning
confidence: 99%
“…The main component of natural gas is CH4 which itself is a GHG but can be used in green energy applications which have been a focus of researchers owing to their high efficiency and low emissions [13][14][15][16]. The CH4 is usually converted to syngas using steam methane reforming [17], dry reforming [18][19][20], and partial oxidation of methane (POM) [4, [21][22][23]. Both the reforming processes are very endothermic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A vast number of catalysts have been studied and proposed for POM to syngas [3,4,21,24,[26][27][28]. Kobayashi et al [27] used Rh/zeolite catalyst and were able to obtain conversion of 84% with a H2/CO ratio of 2.0 at 600 °C and the catalytic performance further improved with the addition of cobalt [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation